Research progress on ethanol-degrading microorganisms and their anti-alcohol products - CAO Jinghua, LI Tianxin, LIU Rui, ZHU Zhengjun, LI Li, WANG Jiangbo (Zhongguo niangzao)
Alcoholism is a disease resulting from excessive ethanol intake and inadequate metabolism within a short period of time. Acute alcoholism can lead to brain dysfunction and even fatality, while chronic alcoholism is closely associated with metabolic disorders such as cardiovascular and cerebrovascular diseases, as well as liver diseases. The intervention of ethanol metabolism through microorganisms presents a potentially safe, cost- effective, and efficient approach. Ethanol-degrading microorganisms have the ability to metabolize ethanol by producing enzymes and enhancing enzyme expression in the body, or they can inhibit ethanol absorption by restoring intestinal flora homeostasis, reducing intestinal permeability, and promoting antioxidant activity to mitigate alcoholic liver injury. The ways, characteristics of microbial degradation of ethanol and the function and characteristics of related anti-alcohol products were reviewed, aiming to establish a theoretical foundation for future research.